THE INFLUENCE OF BUSINESS CAPITAL AND THE QUALITY OF HUMAN RESOURCES (HR) ON THE PERFORMANCE OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN KARANG ANYAR VILLAGE - Farhan Aliansyah; Hendri Dunan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Evaluation of the results or achievements of a business in achieving its goals and targets is called business performance. During the operation process, MSMEs face obstacles such as limited low human resources and business capital This study aims to examine how the performance of MSMEs in Karanganyar Village is influenced by the quality of human resources that can be found in business. This study uses a quantitative approach, the main data obtained from a questionnaire that will be distributed to 30 respondents and the classical assumption test of multiple linear analysis is aimed at analyzing the data and the results of this study prove that the existence of working capital (X1) does not affect business performance (Y), where the significant value of 0.156 > 0.05, and the quality of human resources (X2) affects the business performance of MSMEs in Karang Anyar Village (Y),  where significant values are 0.042 < 0.05.